2022
DOI: 10.1590/0103-8478cr20201054
|View full text |Cite
|
Sign up to set email alerts
|

Genotype plus genotype by-environment interaction biplot and genetic diversity analyses on multi-environment trials data of yield and technological traits of cotton cultivars

Abstract: Understanding the genetic diversity and overcoming genotype-by-environment interaction issues is an essential step in breeding programs that aims to improve the performance of desirable traits. This study estimated genetic diversity and applied genotype + genotype-by-environment (GGE) biplot analyses in cotton genotypes. Twelve genotypes were evaluated for fiber yield, fiber length, fiber strength, and micronaire. Estimation of variance components and genetic parameters was made through restricted maximum like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The description provided by MINAM [ 2 ] did not report the presence of G. hirsutum L. in the region of Cusco; however, in the regions of Cajamarca, Lambayeque, and Pasco, these species can be found. On the other hand, it is known that G. hirsutum L. is an introduced and cultivated species [ 28 ]; its origin is Mexico [ 9 ], and its fiber is very important for the countries that cultivate it [ 10 , 21 ]. The accounts of the natives living in these localities confirmed the use of this species and showed the importance of these cotton species among indigenous communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The description provided by MINAM [ 2 ] did not report the presence of G. hirsutum L. in the region of Cusco; however, in the regions of Cajamarca, Lambayeque, and Pasco, these species can be found. On the other hand, it is known that G. hirsutum L. is an introduced and cultivated species [ 28 ]; its origin is Mexico [ 9 ], and its fiber is very important for the countries that cultivate it [ 10 , 21 ]. The accounts of the natives living in these localities confirmed the use of this species and showed the importance of these cotton species among indigenous communities.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the diversity of cotton is important, as Gossypium is a genus that easily hybridizes through genotype–environment interactions (G×E) [ 20 , 21 ]. Diversity studies are important and provide new knowledge that makes it possible to improve and recover native cottonwoods; they also deepen our understanding of how species have adapted to different environments [ 20 , 21 , 22 ]. In the case of Lower and Upper Urubamba in the province of La Convención-Cusco, hybridization is already occurring, as demonstrated in recent studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple genes control fiber quality traits with a negative relationship with productive potential, which has often restricted advances in improving the fiber quality of new commercial varieties (Arriel et al., 2023; Hayat & Bardak, 2020; Ijaz et al., 2019; Li et al., 2022; Liu et al., 2020). Furthermore, some studies have reported that commercial upland cotton cultivars are losing some fiber quality characteristics, such as fiber strength (Hinze et al., 2016; Peixoto et al., 2022). In this context, the genetic breeding of fiber quality depends on exploring and efficiently using available plant genetic resources (He et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…High performance of genotype under different environmental conditions is a most important goal in breeding program, therefore the interaction must be consider through testing potential ability under different environmental conditions [5]. GGE biplot analysis use principal component analysis in explanations the differences among genotypes in terms of figures illustrate variability caused differences in traits in terms of stability parameters [6,7]. Seed cotton yield and it's components almost aren't congruent in their performance in different environments [8,9].…”
Section: Introductionmentioning
confidence: 99%